The Impact of the Free Meal Program on the Improvement of Academic Achievement of Elementary School Students: A Case Study at SDN 31 Palembang - Muhammad Al Fazri; Putri Nabila; Suwandi (The Future of Education Journal, 2025)
This study examines the impact of the free meal program on the academic achievement of elementary school students at SDN 31 Palembang. The background of this research stems from the fact that meeting nutritional needs, as a component supporting learning success, is very important. The research utilized a descriptive qualitative approach, including document analysis of student grades before and after the program implementation, direct observations, and interviews with teachers. The results indicate that providing students with nutritious meals regularly improves their concentration, memory, and motivation to learn. Additionally, this program helps students from different economic backgrounds gain better education and develop healthy eating habits. In conclusion, the free meal program has a positive social and academic impact and can be used to enhance education. To ensure that students benefit in the long term, this study recommends continuous evaluation of the food quality and program sustainability.